+TV4E: Interactive Television as a Support to Push Information about Social Services to the Elderly - Silva, T. (2016)
Ageing is a global phenomenon that in the last decades has led to a significant inversion of the ageing pyramid in the developed societies. This fact has been introducing deep changes in societies leading to increase attention towards seniors’ concerns and needs and has leverage the appearance of multiple gerontechnologies. In this context television as an enabler technology is a promising option for the elderly, enabling to serve this population segment through features such as distance help, support of services that promote social interaction or provision of medical information. Despite the important investments that have been done by the State for the dissemination of such services, the existent technical solutions are mostly web-based, implying a “pull-oriented” activity rather than the “push-oriented” informative dynamic that most seniors are familiarized. In this paper we discuss the key set of features of an iTV application, aiming to enrich the television experience with interleaved informative content personalized to the user's profile. Also a special attention is given to the state of the art in the field of gerontechnologies enabled by interactive television systems in order to identify the gaps in features related with public and social services information spreading.